Harrington function as an integral approach to assessing food security in Russia - Qian Xinyi; Salikov Yu.A.; Kolomytseva O.Yu.; Maslov A.V. (BIO Web of Conferences)
In accordance with the new doctrine of food security of the Russian Federation, which includes 14 key indicators, a comprehensive analysis of the level of food security in Russia for 2019–2023 was conducted. A surrogate function based on the Harrington function was used for the analysis. Using a standard Excel program, a linear equation with a high degree of correlation with the Harrington function was determined, which allowed ensuring the accuracy of calculations. In order to standardize the data and their dimensionless transformation, the method of linear scaling was applied, which allowed deriving an individual linear equation for each indicator. On the basis of the obtained data, a universal integral indicator was developed, which allows for a comprehensive assessment of food security. The results of the analysis showed that the level of food security in Russia during the period under study was at an average level. The minimum value was recorded in 2021 (0.415), the maximum in 2022 (0.552). The dynamics of the indicators emphasizes the importance of developing measures aimed at eliminating risks and strengthening the sustainability of the food system in the long term.